Biodegradation of phenol by the yeast candida tropicalis: an investigation by NMR spectroscopy - Phalgune, U. D.; Rajamohanan, P. R.; Gaikwad, B. G.; Varma, R. J.; George, S. (Applied Biochemistry and Biotechnology, 2013)
The process of phenol biodegradation by the yeast Candida tropicalis NCIM 3556 in aqueous medium was studied by H-1, C-13, and DOSY NMR techniques. Samples at regular intervals were centrifuged to separate the cells, and H-1 spectral data were collected at 400 MHz. Though a gradual decrease in the concentration of phenol was observed, after an incubation period of similar to 8 h, formation of any intermediate products could not be detected. Experiments carried out with uniformly C-13-labeled phenol also failed to detect formation of any carboxylic acid intermediates during degradation. The studies indicated that the phenol was completely degraded to carbon dioxide and water in approximately 20 h. Self-diffusion coefficient measurements showed that the lifetime of phenol in the bound form is too small to impart any change in its diffusion behavior and the intermediates formed are converted to carbon dioxide and water at a very fast rate.
Keywords: biocatalysis; Carboxylic acid; Diffusion; Enzyme; NMR spectroscopy; phenol

C-C Bond formation catalyzed by natural gelatin and collagen proteins - Kuehbeck, Dennis; Dhar, Basab Bijayi; Schoen, Eva-Maria; Cativiela, Carlos; Gotor-Fernandez, Vicente; Diaz, David Diaz (Beilstein Journal of Organic Chemistry, 2013)
The activity of gelatin and collagen proteins towards C-C bond formation via Henry (nitroaldol) reaction between aldehydes and nitroalkanes is demonstrated for the first time. Among other variables, protein source, physical state and chemical modification influence product yield and kinetics, affording the nitroaldol products in both aqueous and organic media under mild conditions. Significantly, the scale-up of the process between 4-nitrobenzaldehyde and nitromethane is successfully achieved at 1 g scale and in good yield. A comparative kinetic study with other biocatalysts shows an increase of the first-order rate constant in the order chitosan < gelatin < bovine serum albumin (BSA) < collagen. The results of this study indicate that simple edible gelatin can promote C-C bond forming reactions under physiological conditions, which may have important implications from a metabolic perspective.
Keywords: biocatalysis; carbon-carbon bond formation; gelatin; Henry reaction; protein

Regioselective and efficient enzymatic synthesis of antimicrobial andrographolide derivatives - Patil, Harshal S.; Jadhav, Dipesh D.; Paul, Ajay; Mulani, Fayaj A.; Karegaonkar, Shrikant J.; Thulasiram, Hirekodathakallu V. (Bioorganic & Medicinal Chemistry Letters, 2018)
Labdane diterpene andrographolide (1) is a major constituent of Andrographis paniculata and known to exhibit wide spectrum of biological activities. In this study, regioselective monoesters of (1) have been synthesized by using Amano lipase AK (Pseudomonas fluorescens) as a biocatalyst. Amano lipase AK was able to execute highly efficient esterification of hydroxyl group attached to C-14 carbon of (1) in presence of acyl donors. Among the various synthesized derivatives including two novel compounds such as andrographolide-14-propionate (3) and andrographolide-14-caproate (5) displayed antimicrobial activity against Staphylococcus aureus with low minimal inhibitory concentration (MIC) 4 mu g/mL and 16 mu g/mL respectively. Furthermore, they have shown low hemolysis activity at their respective MIC and increase in the permeability of the bacterial cell membrane as delineated by FITC uptake and SEM imaging studies. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Acylation; Andrographolide; Antimicrobial activity; biocatalysis; Hemolysis; Lipase; Natural product

Integrated chemo and bio-catalyzed synthesis of 2,5-furandicarboxylic acid from fructose derived 5-hydroxymethylfurfural - Parate, Roopa D.; Dharne, Mahesh S.; Rode, V. Chandrashekhar (Biomass & Bioenergy, 2022)
Biomass being a renewable source of energy, has emerged as an attractive target for manufacturing valuable products. These possibilities can be explored to meet the current need for degradable plastic, 2,5-furandicarboxylic acid (FDCA). Integration of chemical and biological approaches for direct biomass conversion into FDCA was evaluated in this study. 5-hydroxymethylfurfural (5-HMF) was chemo-catalytically obtained from fructose using recyclable amberlyte IR-120 as a catalyst with >98% purity. Klebsiella oxytoca NCIM 2694 bacterial strain showed the potential of converting 98% of 5-HMF into FDCA with 58% selectivity at 96 h. With optimized conditions of pH 7, 37 degrees C, 2 g whole cells, we reported 99% 5-HMF conversion to FDCA with 95% selectivity at 72 h and 2667 mg L-1 yield, with 39 mg L-1 h-1 productivity. This is the highest yield obtained with the substrate concentration as high as 3000 mg L-1 reported till date. While the bacterial tolerance to 5-HMF observed was for the highest 5-HMF concentration of 4000 mg L-1, with 99% conversion however, compromising the FDCA yield to 2447 mg L-1 and 32 mg L-1 h-1 productivity. Atom economy of 85% and E factor of 17.71 g g-1 was obtained as a measure of its efficiency and sustainability of the process. The developed process will decrease the cost by excluding any extra nutrient supplement, complete substrate utilization, highest FDCA selectivity/productivity and higher tolerance by K. oxytoca, sequentially catalyzing the oxidations by a single route for FDCA synthesis from renewables.
Keywords: biocatalysis; Biodegradable polyester; Biomass; Platform chemical; Sustainability metrics

Bioinspired nanochitin-based porous constructs for light-driven whole-cell biotransformations - Arumughan, Vishnu; Medipally, Hitesh; Torris, Arun; Leva, Tuukka; Grimm, Hanna C.; Tammelin, Tekla; Kourist, Robert; Kontturi, Eero (Advanced Materials, 2025)
Solid-state photosynthetic cell factories (SSPCFs) are a new production concept that leverages the innate photosynthetic abilities of microbes to drive the production of valuable chemicals. It addresses practical challenges such as high energy and water demand and improper light distribution associated with suspension-based culturing; however, these systems often face significant challenges related to mass transfer. The approach focuses on overcoming these limitations by carefully engineering the microstructure of the immobilization matrix through freeze-induced assembly of nanochitin building blocks. The use of nanochitins with optimized size distribution enabled the formation of macropores with lamellar spatial organization, which significantly improves light transmittance and distribution, crucial for maximizing the efficiency of photosynthetic reactions. The biomimetic crosslinking strategy, leveraging specific interactions between polyphosphate anions and primary amine groups featured on chitin fibers, produced mechanically robust and wet-resilient cryogels that maintained their functionality under operational conditions. Various model biotransformation reactions leading to value-added chemicals are performed in chitin-based matrix. It demonstrates superior or comparable performance to existing state-of-the-art matrices and suspension-based systems. The findings suggest that chitin-based cryogel approach holds significant promise for advancing the development of solid-state photosynthetic cell factories, offering a scalable solution to improve the efficiency and productivity of light-driven biotransformation.
Keywords: biocatalysis; light-driven biotransformation; nanochitins; porous materials